Synthesis and Anti-Microbial Activity of 3-Hydrazinyl-7- Ethylquinoxaline-2(1h)-Thiol Derivatives - Teli, Sangappa; Teli, Dharyappa (Asian Journal of Pharmaceutical Research and Development, 2023)
There are various pharmaceutical applications for quinoxaline derivatives. Benzoheterocycles, 6-methylequinoxalin-2,3-diones, and 3-Hydrazinyle are quinoxaline derivatives. 7-Methoxyquinoxaline-2(1H)-thiol Derivatives TLC, Melting Point, FT-IR, and 1HNMR are used to describe quinoxaline compounds such as SG-IA, SG-IB, SG-IC, SG-ID, SG-IE, and SG-IF. Biological activity data showed that SG-IC and SG-IB were moderately active, whereas SG-IA, SG-ID, SG-IE, and SG-IF had average activity when compared to the standard. The test compounds were discovered to be more sensitive to Gram-positive bacteria such as Staphylococcus aureus and Escherichia coli (Gram-negative bacteria).